2015
DOI: 10.1007/s00787-015-0765-6
|View full text |Cite
|
Sign up to set email alerts
|

Salivary oxytocin in adolescents with conduct problems and callous-unemotional traits

Abstract: Callous-unemotional (CU) traits correlate with the severity and prognosis of conduct disorder in youth. The neuropeptide oxytocin (OT) has been linked to prosocial behaviors, including empathy and collaboration with others. This study discusses a possible role for OT in the biology of delinquent behavior. We hypothesized that in delinquent youth OT secretion will correlate with the severity of conduct problems and specifically with the level of CU traits. The study group included 67 male adolescents (mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…In general, however, oxytocin signals the presence of a socially relevant stimulus that requires attention and ultimately promotes social affiliation [66•]. The association between oxytocin and prosocial behavior has not been measured during adolescence, although one study shows that adolescent males with higher salivary oxytocin levels report fewer conduct problems [82], which can be cautiously interpreted as more prosocial behavior. Finally, one study reported elevated oxytocin levels in adolescents with treatment-resistant MDD, compared to non-treatment resistant and healthy control adolescents [83•].…”
Section: Oxytocin and Testosteronementioning
confidence: 99%
“…In general, however, oxytocin signals the presence of a socially relevant stimulus that requires attention and ultimately promotes social affiliation [66•]. The association between oxytocin and prosocial behavior has not been measured during adolescence, although one study shows that adolescent males with higher salivary oxytocin levels report fewer conduct problems [82], which can be cautiously interpreted as more prosocial behavior. Finally, one study reported elevated oxytocin levels in adolescents with treatment-resistant MDD, compared to non-treatment resistant and healthy control adolescents [83•].…”
Section: Oxytocin and Testosteronementioning
confidence: 99%
“…Saliva is easy to obtain and the neuropeptides in saliva are reliably measurable . Therefore, salivary biomarkers increase in popularity and are used in a growing number of studies examining different patient populations . In a recent study on neurocritical care patients, we demonstrated a moderate to strong correlation for OXT between the saliva and CSF compartment, whereas plasma OXT did not correlate well with CSF levels .…”
Section: Discussionmentioning
confidence: 77%
“…We were able to find only two studies focused on the role of the oxytocinergic system in assessing the behavior of children that were conducted using the SDQ questionnaire. In their study, Levy et al showed that the concentration of oxytocin in saliva was negatively correlated with the severity of behavioral problems identified by the SDQ questionnaire in 16 -year-old adolescent boys admitted to psychiatric counseling because of antisocial behavior [47]. It was also found that OT production was reduced in adolescents with insufficient emotional response and an unemotional type of character.…”
Section: Discussionmentioning
confidence: 96%